Eroding online Violence Towards Indonesian Women During Covid-19 - Gultom, Eva Solina (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—The coronavirus has fully motivated a number of regions in Indonesia to implement Large-Scale General Restrictions (PSBB). This policy may be the right solution. However, it also brings with it a recent dilemma embracing women. PSBB has influenced individuals to limit their physical mobility and move them to use high dependence on technology platforms including the web or social media. The intensity and repetition of social media use leads to online aggression compared to the case of women. The Jakarta Women's Legal Aid Institute noted that there were 30 cases of online violence against women in Indonesia in March and April 2020. Unfortunately, this number continues to increase from year to year. Many forms of online sex-based violence exist and most of them aim to intimidate, humiliate, and dominate women. Some of them are online sexual harassment, fear of sharing personal content with exploitation themes, dating violence, and online extortion. Surprisingly, not all women in Indonesia understand and report these forms of violence to the National Commission for the Protection of Women or related agencies due to the lack of information and socialization from local governments during the pandemic. As a result, this issue marks a long list of solutions involving governments and the private sector to make online violence worse. This paper will explicitly show the importance of eradicating online violence against women during the Coronavirus in Indonesia. Courage to speak is needed. Community support to exercise their right to vote is very important to voice positive things and stop violence against women. Keywords: covid-19,gender, Indonesia, online violence, woman Abstrak—Virus corona telah mendorong sejumlah daerah di Indonesia untuk menerapkan Pembatasan Sosial Berskala Besar (PSBB). Kebijakan ini mungkin bisa menjadi solusi yang tepat. Namun, hal tersebut dapat menjadi dilemma bagi perempuan. PSBB telah mempengaruhi setiap individu untuk membatasi mobilitas fisik dan menggerakkan masyarakat untuk memiliki ketergantungan tinggi terhadap teknologi, seperti internet atau media sosial. Jumlah intensitas dan penggunaan media social yang semakin meningkatkian harinya, mengarah kepada agresi online terhadap perempuan. Lembaga Bantuan Hukum Perempuan Jakarta mencatat ada 30 kasus kekerasan online terhadap perempuan di Indonesia pada Maret dan April 2020. Sayangnya, jumlah ini terus meningkat dari tahun ketahun. Ada banyak bentuk kekerasan berbasis seks online dan mayoritas diantaranya bertujuan untuk mengintimidasi, mempermalukan, untuk membagikan konten pribadi yang mengarah kepada eksploitasi, kekerasan dalam berpacaran, dan pemerasan online. Anehnya, tidak semua perempuan di Indonesia memahami dan melaporkan bentuk-bentuk kekerasan tersebut ke Komnas Perempuan atau instansi terkait karena minimnya informasi dan sosialisasi dari pemerintah daerah selama pandemi. Akibatnya, masalah ini menandai daftar panjang dan solusi terhadap buruknya kekerasan online yang melibatkan pemerintah dan sektor swasta. Tulisan ini secara eksplisit akan menunjukkan pentingnya pemberantasan kekerasan online terhadap perempuan selama virus Corona di Indonesia. Dibutuhkan keberanian untuk berbicara. Dukungan masyarakat untuk menggunakan hak pilihnya sangat penting untuk menyuarakan hal-hal positif dan menghentikan kekerasan terhadap perempuan. Kata kunci: covid-19, gender, Indonesia, kekerasan online, perempuan